2019
DOI: 10.1371/journal.pntd.0007300
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis-associated epilepsy in the Democratic Republic of Congo: Clinical description and relationship with microfilarial density

Abstract: Background High epilepsy prevalence and incidence were observed in onchocerciasis-endemic villages in the Democratic Republic of Congo (DRC). We investigated the clinical characteristics of onchocerciasis-associated epilepsy (OAE), and the relationship between seizure severity and microfilarial density. Methods In October 2017, ivermectin-naive persons with epilepsy (PWE) were recruited from onchocerciasis-endemic areas in the Logo health zone in the DRC. Additional PWE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Most likely the advantage of the multiple dose ivermectin is explained by the lower mf density by the end of the study period in participants on a multiple dose ivermectin regimen, confirming the previously documented positive association between seizure frequency and mf density [14]. Our findings strongly suggest that O. volvulus mf may induce seizures and that the beneficial effect of ivermectin was not caused by a direct anti-seizure mechanism.…”
Section: Discussionsupporting
confidence: 87%
“…Most likely the advantage of the multiple dose ivermectin is explained by the lower mf density by the end of the study period in participants on a multiple dose ivermectin regimen, confirming the previously documented positive association between seizure frequency and mf density [14]. Our findings strongly suggest that O. volvulus mf may induce seizures and that the beneficial effect of ivermectin was not caused by a direct anti-seizure mechanism.…”
Section: Discussionsupporting
confidence: 87%
“…However, the penetration of ivermectin into murine CNS must be interpreted in the light of evidence demonstrating an increased permeability of their blood-brain barrier (BBB) during the neonatal period [20]. Ivermectin given at therapeutic doses is unlikely to cross the human BBB [21] and therefore cannot elicit a direct anti-epileptic effect in the CNS The relative superiority of the multiple dose ivermectin in reducing seizures during our study is probably explained by the lower mf density at the end of the study period in participants on this regimen, thus confirming the previously documented positive association between seizure frequency and mf density [22]. A small study conducted in a non-onchocerciasis-endemic area reported that treatment with ivermectin decreased the frequency of seizures in persons with refractory epilepsy [23].…”
Section: Discussionsupporting
confidence: 85%
“…Most cases of NS have been described in the onchocerciasis-endemic regions in northern Uganda [3,6], western Uganda [7], South Sudan [8], and the Mahenge area in Tanzania [9]. More recent studies have reported nodding seizures among persons with epilepsy (PWE) in the onchocerciasis-endemic regions in Cameroon [10] and the Democratic Republic of Congo [11]. A high prevalence of epilepsy has also been reported in many onchocerciasis meso-and hyper-endemic regions [12][13][14][15] particularly where transmission is poorly controlled [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%